DISEASES OF THE ORAL CAVITY AND TEETH, PREVENTION OF DISEASES OF THE ORAL MUCOSA - Raxmonova Shoxsanom (Scholars Digest Publishing, 2024)
Periodontal diseases are among the most common dental diseases and occur in 80% of children and almost the entire adult population. Periodontal is a complex of tissues: tooth, periodontal, alveolar part of the jaw, gum. Pathological processes may have an inflammatory dystrophic (or a combination of them) character.
Keywords: oral cavity, teeth, diseases of the oral mucosa, modern medical treatment, medical help.